Ortaokul Öğrencileri İçin Masa Tenisi Bilgi Testinin Geçerlik ve Güvenirliği: Metodolojik Çalışma. - DOĞAN, Vedat; DEVRİLMEZ, Erhan; DERVENT, Fatih (Turkiye Klinikleri Journal of Sports Sciences, 2025)
Objective: It is expected that secondary school students should have sufficient knowledge about rules, techniques and tactics through sport and physical activity courses which they have learned in physical education and sport courses. The measurement tools which examine knowledge levels of secondary school students, who completed these courses, are required. The purpose of this study was to develop table tennis knowledge test for secondary school students. Material and Methods: There were 6th grade (n=79), 7th grade (n=60) and 8th grade (n=51) 103 boys and 87 girls, totally 190 students from 6 public secondary schools were voluntarily accepted to participate in this study. Age range of them was from 12 to 14 years (X=12.85, standard deviation= 1.77). Table tennis knowledge test was developed in 4 steps. There was 1 program development specialist, 1 high level table tennis coach, 2 elite table tennis players and 1 physical education teacher who teach table tennis in school physical education lesson. At the end of the development process, draft table tennis knowledge test included 10 rules, 3 techniques and 2 tactics, totally 15 questions. To check validity and reliability of draft test, Rasch modelling was utilized. Results: Totally 14 questions out of all questions were ensured the acceptable range for infit and outfit values. Item and person separation index values were within acceptable range. Conclusion: Fourteen questions of developed 15 questions table tennis knowledge test was determined as valid and reliable knowledge test. It is advised to use this knowledge test for measuring table tennis knowledge level of secondary school students.